Analysis Of Slang Words Used In “Deadpool & Wolverine” Movie - Butar, Maya Citra Herawati; Elfrida, Rotua; Rajagukguk, Rosdiana (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to identify the types and meanings of slang in movies. Using the descriptive-qualitative method, the writer analyzed the movie based on the theory of slang words used by Allan and Burridge (2006) as a reference, and the data was taken from the dialogue in the movie script. The results found 129 slang terms divided into five types: fresh and creative (45), flippant (54), imitative (10), acronym (3), and clipping (17). The most dominant type of slang word is flippant, which means many words are used in a casual or careless way, often to create humor, sarcasm, or lighthearted expressions spoken by characters. The analysis shows that each type supports the characterization and dynamics of character interactions. The meanings of the slang words found in the movie are diverse, but the slang words are mostly used in informal situations. In conclusion, the meanings of slang words found in the movie are diverse but mostly in informal situations.